Docking protein-1 promotes inflammatory macrophage signaling in gastric cancer. (2nd November 2019) - Li, Tong; Li, Beifang; Sara, Asgharpour; Ay, Christine; Leung, Wing Yan; Zhang, Yanquan; Dong, Yujuan; Liang, Qiaoyi; Zhang, Xiang; Weidner, Philip; Gutting, Tobias; Behrens, Hans-Michael; et al.
ABSTRACT: Docking protein-1 (DOK1) is a tumor suppressor frequently lost in malignant cells, however, it retains the ability to control activities of immune receptors in adjacent stroma cells of the tumor microenvironment. We therefore hypothesized that addressing DOK1 may be useful for cancer immunotherapy. DOK1 mRNA and DOK1 protein expression were downregulated in tumor cells of gastric cancer patients (n = 249). Conversely, its expression was up-regulated in cases positive for Epstein Barr Virus (EBV+) together with genes related to macrophage biology and targets of clinical immunotherapy such as programmed-cell-death-ligand-1 (PD-L1). Notably, high DOK1 positivity in stroma cells conferred poor prognosis in patients and correlated with high levels of inducible nitric oxide synthase in CD68+ tumor-associated macrophages. In macrophages derived from human monocytic leukemia cell lines, DOK1 (i) was inducible by agonists of the anti-diabetic transcription factor peroxisome proliferator-activated receptor-gamma (PPARγ), (ii) increased polarization towards an inflammatory phenotype, (iii) augmented nuclear factor-κB-dependent transcription of pro-inflammatory cytokines and (iv) reduced PD-L1 expression. These properties empowered DOK1+ macrophages to decrease the viability of human gastric cancer cells in contact-dependent co-cultures. DOK1 also reduced PD-L1 expression in human primary blood monocytes. Our data propose that the drugability of DOK1 may be exploited to reprogram myeloid cells and enforce the innate immune response against EBV+ human gastric cancer.